Intraspecific Variation of the Aquatic Fungus Articulospora tetracladia: An Ubiquitous Perspective - Seena, Sahadevan; Duarte, Sofia; Pascoal, Cláudia; Cássio, Fernanda (PLOS ONE, 2012)
The worldwide-distributed aquatic fungus Articulospora tetracladia Ingold is a dominant sporulating species in streams of the Northwest Iberian Peninsula. To elucidate the genetic diversity of A. tetracladia, we analyzed isolates collected from various types of plant litter or foam in streams from North and Central Portugal and North Spain, between 2000 and 2010. Genetic diversity of these fungal populations was assessed by denaturing gradient gel electrophoresis (DGGE) fingerprints and by using ITS1-5.8S-ITS2 barcodes. Moreover, ITS1-5.8S-ITS2 barcodes of A. tetracladia reported in other parts of the world (Central Europe, United Kingdom, Canada, Japan and Malaysia) were retrieved from the National Center for Biotechnology (NCBI) and the National Institute of Technology and Evaluation Biological Resource Center (NBRC) to probe into genetic diversity of A. tetracladia. PCR-DGGE of ITS2 region of 50 Iberian fungal isolates distinguished eight operational taxonomic units (OTUs), which were similar to those obtained from neighboring trees based on ITS2 gene sequences. On the other hand, ITS1-5.8S-ITS2 barcodes of 68 fungal isolates yielded nine OTUs, but five fungal isolates were not assigned to any of these OTUs. Molecular diversity was highest for OTU-8, which included only European isolates. Two haplotypes were observed within OTU-8 and OTU-9, while only one haplotype was found within each of the remaining OTUs. Malaysia did not share haplotypes with other countries. Overall results indicate that, apart from the Malaysian genotypes, A. tetracladia genotypes were geographically widespread irrespective of sampling time, sites or substrates. Furthermore, PCR-DGGE appeared to be a rapid tool for assessing intraspecific diversity of aquatic hyphomycetes.